Efficacy of Erythropoietin in treatment of anemia in patients hospitalized in the ICU of Ardabil city hospital - Feizi, Iraj; Norouzi, Vadood (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Several studies have shown that approximately 95% of patients who have been admitted to the ICU are anemic. Anemia in acute patients leads to significant transfusion. Transfusion can lead to significant complications. Because of the risks of transfusion an alternative therapy for anemia in patients seems be a necessary need for its. The aim of this study was to investigate the efficacy of Erythropoietin in treatment of anemia in patients hospitalized in the ICU of Ardabil city hospital. Methods: This study is a clinical trial. In this study after selection of patients based on inclusion and exclusion criteria, their data were entered in a check list. Patients were divided into two groups of 35 persons randomly. For first group, erythropoietin was administrated in addition of iron and in second group only iron was administrated. All patients were administrated 100 mg of iron. Hematological indexes and clinical status of patients was evaluated and results were analyzed by statistical methods in SPSS version 19. Results: In this study, in cases 65.7% and in controls 71.4% were male. The average age of patients in cases was 61.6±20.8 and controls were 61.02±22.5 years. The mean duration of hospitalization in internal ICU was 37.73 days and in surgical ICU was 21.35 days and was observed that at baseline the hemoglobin levels in internal patients was lower than surgical patients (p=0.023). 80% of patients in case group (5.8 units) and 88.57% of patients in controls (6.3 units) required blood transfusion. The hemoglobin level in erythropoietin receiving group increased significantly compared to the control group. Conclusions: The results of this study showed that erythropoietin is an effective drug to increase hemoglobin level and can provide a significant increase in hemoglobin level compared to placebo.